2018
DOI: 10.15171/jhp.2018.24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of massage therapy and aromatherapy on fatigue in patients with knee osteoarthritis

Abstract: Aromatherapy (Lavender essential oil) significantly reduced fatigue in patients with knee osteoarthritis. Thus, due to the high prevalence of knee osteoarthritis, this method is recommended to patents with osteoarthritis because of its availability, security, and cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Massage is a maneuver using manual movements that are applied softly to the superficial tissues that can have effects on the nervous, muscular, local, and general circulation, lymph, and respiratory tract, including hand-operated procedures, pressing, rubbing and massaging [9]. Massage effects are remarkable for both reflective and mechanical aspects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Massage is a maneuver using manual movements that are applied softly to the superficial tissues that can have effects on the nervous, muscular, local, and general circulation, lymph, and respiratory tract, including hand-operated procedures, pressing, rubbing and massaging [9]. Massage effects are remarkable for both reflective and mechanical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Massage effects are remarkable for both reflective and mechanical aspects. Mechanical effects improve muscle pumping, stretch in soft tissues, prevent adhesion, increase capillary circulation, increase tissue elasticity, and improve tissue permeability, and its reflective effects include relaxation and opening of blocked capillary circulation and eventually increased blood flow [9, 26]. The results of some studies on the effect of massage on various diseases such as knee osteoarthritis, chronic neck pain, back pain, and muscle cramp pain in hemodialysis patients indicated its positive effect [27, 28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing knowledge and experience is very important in aromatherapy and nurses have contributed to this field by investigating the potential effects of aromatherapy and essential fats in several areas, such as gestation, maternal and fetal health, dysmenorrhea, pain, intensive care, cancer, gastrointestinal, nervous, respiratory diseases and mental health (Cho, Min, Hug, & Lee, ; Kim, Nam, & Paik, ; Maddocks‐Jennings & Wilkinson, ). There are studies that have shown that aromatherapy decreases pain, fatigue, anxiety and sleep disorders (Cho et al, ; Kabiri, HasanPour‐Dehkordi, & Deris, ; Kim et al, ; Lee, Choia, Posadzki, & Ernst, ). Studies conducted on elderly individuals have shown that aromatherapy could be applied effectively and safely.…”
Section: Introductionmentioning
confidence: 99%